CO2 sequestration in two mediterranean dune areas subjected to a different level of anthropogenic disturbance. (5th September 2017) - Bonito, Andrea; Ricotta, Carlo; Iberite, Mauro; Gratani, Loretta; Varone, Laura
Abstract: Coastal sand dunes are among the most threatened habitats, especially in the Mediterranean Basin, where the high levels of human pressure impair the presence of plant species, putting at risk the maintenance of the ecosystem services, such as CO2 sequestration provided by these habitats. The aim of this study was to analyze how disturbance-induced changes in plant species abundance patterns account for variations in annual CO2 sequestration flow (CS) of Mediterranean sand dune areas. Two sites characterized by a high (site HAD) and a lower (site LAD) anthropogenic disturbance level were selected. At both sites, plant species number, cover, height and CS based on net photosynthesis measurements were sampled. At the plant species level, our results highlighted that Ammophila arenaria and Pancratium maritimum, had a key role in CS. Moreover, the results revealed a patchy species assemblage in both sites. In particular, HAD was characterized by a higher extension of the anthropogenic aphytoic zone (64% of the total transect length) than LAD. In spite of the observed differences in plant species composition, there were not significant differences between HAD and LAD in structural and functional traits, such as plant height and net photosynthesis. As a consequence, HAD and LAD had a similar CS (443 and 421 Mg CO2 ha −1 y −1, respectively). From a monetary point of view, our estimates based on the social costs of carbon revealed that the flow of sequestered CO2 valued on an average 3181 ± 114 ha −1 year −1 (mean value for the two sites). However, considering also the value of the CO2 negative flow related to loss of vegetated area, the annual net benefit arising from CO2 sequestration amounted to 1641 and 1772 for HAD and LAD, respectively. Overall, the results highlighted the importance to maximize the efforts to preserve dune habitats by applying an effective management policy, which could allow maintaining also a regulatory ecosystem service such as CO2 sequestration. Highlights: Plant height is the most significant variable accounting for the ability to predict CO2 sequestration. The species colonizing mobile dunes have a key role in CO2 sequestration. The annual net benefit arising from CO2 sequestration amounted to 1707 ± 93.